2007
DOI: 10.1002/ijc.23064
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient dietary patterns and the risk of breast and ovarian cancers

Abstract: The issue of diet and breast and ovarian cancers has been considered in terms of foods and nutrients, but rarely in terms of dietary patterns. We examined the associations between dietary patterns and breast and ovarian cancers in 2 Italian multicentric case-control studies. Cases were 2,569 breast cancers and 1,031 ovarian cancers hospitalized in 4 Italian areas between 1991 and 1999. Controls were 3,413 women from the same hospital network. Dietary habits were investigated through a validated food-frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
63
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 39 publications
8
63
0
Order By: Relevance
“…The E3N-EPIC prospective cohort study has also found that a 'Western-alcohol' pattern characterized by meat products, French fries, appetizers, rice/pasta, potatoes and canned fish may be positively associated with breast cancer risk (hazard ratio 5 1?20, 95 % CI 1?03, 1?38) among French women (4) . Only two studies have found that a 'pork, processed meat and potato' dietary pattern (relative risk 5 0?69, 95 % CI 0?52, 0?92) (6) and an 'animal products' pattern (OR 5 0?74, 95 % CI 0?61, 0?91) (15) have negative associations with breast cancer risk, while other cohort studies have failed to show any significant relationship (7,(10)(11)(12)(13)16) . Several biological mechanisms may explain the positive association between unhealthy dietary patterns and breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…The E3N-EPIC prospective cohort study has also found that a 'Western-alcohol' pattern characterized by meat products, French fries, appetizers, rice/pasta, potatoes and canned fish may be positively associated with breast cancer risk (hazard ratio 5 1?20, 95 % CI 1?03, 1?38) among French women (4) . Only two studies have found that a 'pork, processed meat and potato' dietary pattern (relative risk 5 0?69, 95 % CI 0?52, 0?92) (6) and an 'animal products' pattern (OR 5 0?74, 95 % CI 0?61, 0?91) (15) have negative associations with breast cancer risk, while other cohort studies have failed to show any significant relationship (7,(10)(11)(12)(13)16) . Several biological mechanisms may explain the positive association between unhealthy dietary patterns and breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted the analyses on a selected set of 28 major micro-and macronutrients, as in our previous work on breast and ovarian cancers (18). We first evaluated their correlation matrix to determine if it was factorable through both visual inspection of the matrix and statistical procedures such as Bartlett's test of sphericity (using the Z approximation to the χ 2 distribution of the test statistic), Kaiser-MeyerOlkin measure, and individual measures of sampling adequacy (19).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a pattern of nutrients may provide more information about probable underlying mechanisms. In contrast to food patterns, few studies have considered nutrient patterns in relation to chronic diseases [4][5][6][7][8][9][10][11]. The approach of nutrient patterns might provide novel insight into the possible relations between nutrients in the etiology of chronic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Food patterns affect the risk of chronic diseases through nutrient intakes, and it is, most likely, a combination of nutrients, rather than an individual one, that will affect the risk [4][5][6][7][8][9][10][11]. Therefore, a pattern of nutrients may provide more information about probable underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%